2019
DOI: 10.1002/da.22954
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of PTSD and substance use on suicidal ideation and behavior in military personnel: Increased risk from marijuana use

Abstract: Background: The current study examines the unique and interactive effects of posttraumatic stress disorder (PTSD) symptoms and days using alcohol, opioids, and marijuana on PTSD symptoms, suicidal ideation, and suicidal behavior up to 1 year, later in a high-risk sample of military personnel not active in mental health treatment. Methods: Current and former military personnel at risk for suicide (N = 545; M age = 31.91 years, standard deviation = 7.27; 88.2% male) completed self-report measures of PTSD symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…For instance, our patients with recurrent pain reported that they found high CBD products (33%) and high THC products (31%) to be effective in treating their pain symptoms whereas, Ueberall et al's patients were only prescribed nabiximols, a balanced THC:CBD product (15). Our findings that 33% of patients with recurrent pain found high CBD products helpful in treating their pain is novel as to date, the majority of studies investigating the possible relationship between medical cannabis and pain have focused on high THC products (32-34, 36, 37, 66) or balanced THC:CBD products, like nabiximols (15,(38)(39)(40)(41). While there is a significant body of pre-clinical work that has examined CBD's role as an anti-inflammatory agent and analgesic (67)(68)(69)(70)(71)(72)(73)(74), this has not meaningfully translated into clinical investigation yet.…”
Section: Recurrent Painmentioning
confidence: 56%
See 1 more Smart Citation
“…For instance, our patients with recurrent pain reported that they found high CBD products (33%) and high THC products (31%) to be effective in treating their pain symptoms whereas, Ueberall et al's patients were only prescribed nabiximols, a balanced THC:CBD product (15). Our findings that 33% of patients with recurrent pain found high CBD products helpful in treating their pain is novel as to date, the majority of studies investigating the possible relationship between medical cannabis and pain have focused on high THC products (32-34, 36, 37, 66) or balanced THC:CBD products, like nabiximols (15,(38)(39)(40)(41). While there is a significant body of pre-clinical work that has examined CBD's role as an anti-inflammatory agent and analgesic (67)(68)(69)(70)(71)(72)(73)(74), this has not meaningfully translated into clinical investigation yet.…”
Section: Recurrent Painmentioning
confidence: 56%
“…The majority of previous clinical studies have focused on investigating either a high THC, high CBD or balanced THC: CBD product, rather than exploring all three options and identifying which is most effective per medical condition. For example, the scientific evidence for anxiety treatment is primarily derived from the use of investigating high CBD products (26-31), whereas for pain, the majority of data has been generated from either high THC products [synthetic THC (32)(33)(34) or high THC herbal cannabis (35)(36)(37)] or nabiximols (a balanced THC:CBD product) (15,(38)(39)(40)(41). There is also a disparity between the cannabinoid ratios used in pre-clinical and clinical research that requires further data to address.…”
Section: Discussionmentioning
confidence: 99%
“…This complex intersection of trauma, distress, substance use and suicidality has been reported in other high-risk occupations. In a study of military personnel, Allan et al (2018) found that participants with post-traumatic stress disorder (PTSD) symptoms, especially in those who reported marijuana use, were much more likely to report suicidal ideation at 1 month and suicidal behaviour at 11-month follow-up. Police and emergency use personnel in Australia were found to have significant associations between substance use, especially opioids, and suicide attempts (Kyron et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Suicidal ideation, an important predictor for the following suicide attempt and death [4,5], have also been explored in different populations in the world, such as community residents [6,7], military personnel [8,9], college students [10], and occupational populations [11,12]. For occupational populations, we have found many job characteristics that were associated with suicidal ideation in previous studies, such as working hours [13], work conditions [14], shift work [15].…”
Section: Introductionmentioning
confidence: 93%